2016
DOI: 10.1002/lary.26245
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and specific characteristics of the incomplete partition type III anomaly in children

Abstract: 4 Laryngoscope, 127:1663-1669, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…So far, five genes have been identified for X-linked nonsyndromic hearing loss. 4 Cochlear IP-III is the rarest among the X-linked nonsyndromic causes of hearing loss. It is an X-linked recessive disorder caused by mutation of the POU3F4 gene located on chromosome X.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, five genes have been identified for X-linked nonsyndromic hearing loss. 4 Cochlear IP-III is the rarest among the X-linked nonsyndromic causes of hearing loss. It is an X-linked recessive disorder caused by mutation of the POU3F4 gene located on chromosome X.…”
Section: Discussionmentioning
confidence: 99%
“…Inner ear anomalies have been reported in 20% of patients with congenital hearing loss. 4 According to the current literature, inner ear malformations are classified into eight distinct groups. 6 IP-III anomaly represents around 4% of them.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of hearing loss among patients with different types of POU3F4 mutations varied greatly. To date, no correlation was found between certain genotypes and initial auditory phenotype [ 28 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…When present, EVA in these patients seems to be different from that described in DFNB4/Pendred syndrome; Incesulu et al presented four case reports where vestibular aqueducts showed great inter-patient variability, but all were large and symmetrical and become cystic or enlarged from the middle parts to the ends near the vestibule [ 131 ]. Accordingly, Kanno et al identified 6 patients (0.6%) with incomplete partition type 3 and POU3F4 mutations among 1004 children with hearing loss; all of them had an enlargement of the vestibular aqueduct close to the vestibule but not at the operculum; these authors linked this specific finding with an absence of hearing fluctuations in these patients [ 132 ]. Similarly, Anderson et al described two brothers with POU3F4 mutations and dilation of the portion of the vestibular aqueduct close to the vestibule [ 133 ].…”
Section: Genes Involved In Determining Non-syndromic Enlarged Vestibular Aqueductmentioning
confidence: 99%